Oil Price Fluctuations and Job Creation Sectors in East Java Province: Testing for Non-Linearity - Devina Audrey Subagya; Syamad (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
This research intends to trace the effects of fluctuations in Brent and WTI oil prices on the job creation sector of East Java Province. The GARCH (1,1) method is used to track the value of oil price fluctuations and the NARDL method is used to find the magnitude of the asymmetric effects. Data in the form of quarterly time series 2011Q1-2022Q4 is also used in this research. The results of the asymmetric test show that there is a significant positive influence between negative fluctuations in Brent and WTI oil prices on the job creation sector in the short-run and there is a significant negative influence between positive fluctuations in Brent and WTI oil prices in the long-run. The test results have contributed to a more complex theoretical study of the impact of oil price fluctuations on the business sector at the provincial level. The test results have produced effective recommendations for stakeholders in East Java Province, namely policymakers and business actors who need to create and use new alternative fuels in production activities. For example, using domestic oil or renewable energy so that it can reduce dependence on international oil price movements. Policymakers can also implement international oil import tariffs and quotas to curb its use.